A Lightweight ITSM Framework for Balancing Service Value and Cost Efficiency in Digital MSMEs - Marcel, Marcel; Alexander, Jessica (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
This study explores how Indonesian Micro, Small, and Medium Enterprises (MSMEs) manage IT services with limited staff and budgets, proposing that a simpler, lightweight approach to IT service management (ITSM) is more suitable for this context. A mixed-method case study was conducted with four MSMEs in Greater Jakarta—two technology-based and two non-technology-based. Key performance indicators such as response time, downtime, and customer satisfaction were derived from service logs and customer ratings, while semi-structured interviews with owners and staff were analyzed for recurring themes. Results revealed that non-technology-based MSMEs achieved a median response time of 12.5 minutes and an average satisfaction score of 4.55, while technology-based MSMEs had a median response time of 1.8 hours and an average score of 3.95. Technology firms logged approximately seven hours of downtime per month, compared to 1.5 hours in non-tech firms, indicating a trade-off between faster responses and higher satisfaction at the cost of less systematic documentation and control. All MSMEs utilized freemium SaaS tools, marketplace dashboards, limited-service hours, and no dedicated IT staff to minimize costs. The study proposes a lightweight ITSM framework and checklist, adaptable with free tools, for use in MSME incubators and support programs, advancing ITSM literature for resource-constrained businesses.